Distingsi Konseptual Etika, Moral, Nilai, dan Estetika serta Fondasi Normatif Etika Islam - Santalia, Indo; Harun, Hamzah; Al Khair Syam, Akmal (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This study aims to provide a conceptual and philosophical analysis of the distinctions between ethics, morals, values, and aesthetics, while also formulating the normative foundations of Islamic ethics as an integrative ethical system. Employing a qualitative approach with a library research method, the study critically examines both classical and contemporary literature in Western philosophy and Islamic thought. A conceptual-comparative analysis was applied to identify similarities, differences, and intersections among these terms. The findings reveal that ethics represents a normative reflection on human actions, morals relate to socially accepted norms, values serve as guiding principles of behavior, and aesthetics emphasizes the dimension of beauty in art and conduct. Within the Islamic perspective, these concepts are comprehensively integrated, with revelation (the Qur’an and Sunnah) serving as the ultimate foundation. Islamic ethics is characterized as theocentric, holistic, and oriented toward both worldly and eternal well-being. Its core principles include tawhid (monotheism), justice, enjoining good and forbidding evil, and tazkiyat al-nafs (self-purification). Thus, this study affirms that Islamic ethics is not only normative but also practical and highly relevant as a moral framework in addressing contemporary global challenges and the dynamics of modern civilization.